ANALYSIS OF HEAVY METAL GEOCHEMISTRY BEHAVIOR ON SOIL IN THE RIVER OF LAKE MATANO AREA, SOUTH SULAWESI - Iswandi, Adnan; Irfan, Ulva Ria; Alimuddin, Ilham (Universitas Ibn Khaldun Bogor, 2022)
Geologically, the Lake Matano area is an area of laterite deposits, where in these deposits there are heavy metal geochemical elements that can have a negative impact on the environment. This research was conducted in three rivers that surround the area and empties into Lake Matano, with the aim of analyzing the geochemical behavior of heavy metals in soil. The method used includes a literature study and observing the results of previous studies and testing the content of heavy metals with the AAS tool. The results showed the behavior of heavy metals in the soil around Lake Matano in the three rivers where metals that exceeded the critical number were Fe, Mn, Cu, Co, Ni. and which is still below the critical number limit is Cr metal. The presence of heavy metals in the soil at the research site is caused by the results of the disposal of waste from mining activities and anthropogenic activities where the end of the disposal goes directly to the ground so that the heavy metals contained in the disposal will enter the soil and experience contamination in nature so that the existing organic compounds have undergone degradation.